Relationship Between Adolescent Knowledge and Premarital Sexual Behavior - Darah Ifalahma; Liss Dyah Dewi Arini; Salsabilla Fauziyah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Knowledge of premarital sex is important given to adolescents, both through formal and informal education. Adolescents who get the right information about premarital sex will tend to have positive behavior. On the other hand, adolescents who lack knowledge about premarital sex tend to have negative behavior. Objective : The purpose of this study was to determine the relationship between adolescent knowledge with premarital sex behavior. Method : The research method is observational analytic with a cross sectional approach. The research sample was high school students totaling 142 students. The sampling technique used the Probability Sampling. The research instrument used a questionnaire. Analysis of research is Chi Square test. Results : The results showed that the majority of adolescents had good knowledge of premarital sex as many as 117 people (82.4%). The majority of adolescent behavior is not at risk as many as 133 (93.7%). The results of the analysis obtained a value with a significance of p = 0.01 < 0.05 meaning that there is a relationship between adolescent knowledge with premarital sex behavior. Conclusions : The conclusion is that there is a relationship between adolescent knowledge with premarital sex behavior.